EVALUATION OF Co-Mo/Al2O3 CATALYSTS FOR HYDRODESULFURIZATION PREPARED BY THE CHEMICAL VAPOR DEPOSITION TECHNIQUE AND CITRIC ACID ADDITION - Nino Rinaldi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
EVALUATION OF Co-Mo/Al2O3 CATALYSTS FOR HYDRODESULFURIZATION PREPARED BY THE CHEMICAL VAPOR DEPOSITION TECHNIQUE AND CITRIC ACID ADDITION. Sulfided Co-Mo or Ni-Mo based catalysts still have been extensively used in refinery for Hydrodesulfurization (HDS) reaction, which is so-called Co-Mo-S phase as active sites. It is proposed that to obtain near zero sulfur content of fuels in the future is by improving the performance of Co-Mo catalysts. It could be approached with enhancing the amounts of active sites, Co-Mo-S phases, for instance with a sophisticated HDS catalysts preparation such as by a Chemical Vapor Deposition (CVD) technique using Co(CO)3NO as a precursor of Co and by the citric acid addition. It is demonstrated that if MoS2/Al2O3 is exposed to Co(CO)NO3 vapor and subsequently sulfided, Co-Mo-S phases form selectively when the Mo content exceeds monolayer loading. The maximum potential HDS activity of Co-Mo/Al2O3 catalysts also can be obtained by the CVD technique. With the conventional Co-Mo/Al2O3 catalysts, the edges of MoS2 particles are completely occupied by Co atoms around of 4 wt% Co, thus more addition of Co caused blocking of the active sites by over layers of Co sulfide clusters. However, with the citric acid addition, not only the amount coverage of Co atoms is increased, but also a high content of Mo could be also well dispersed (Mo > 20 wt%) on the surface support forms monolayer. In addition, the amount of Co forming Co-Mo-S phases was estimated from the correlation between NO/Mo and Co/Mo ratio by the CVD technique.